PENGUATAN KOMUNIKASI DAN PELAYANAN WISATA RELIGI BERBASIS PEMBERDAYAAN MASYARAKAT DI CAGAR BUDAYA MAKBAROH SYEKH SULTHON RAFIUDIN - Priatna, Achmad Nashrudin; Fithrotul Kamilah; Sanin Sudrajat; Ahmad Suganda; Saepudin, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
The Makbaroh Syekh Sulthon Rafiudin cultural heritage site in Sukasari Village, Tunjung Teja District, is a religious tourism destination with historical, spiritual, and social value for the local community. However, this tourism potential has not been fully maximized due to limited public communication and traditional tourism services. This community service program aims to strengthen the community's capacity to manage religious tourism communications and services through a community empowerment approach. The methods used include outreach, public communication training, tourism service assistance, and strengthening local institutions. The results of the activities indicate an increase in community understanding of effective communication strategies, skills in providing friendly and informative tourism services, and the formation of a shared commitment to preserving cultural heritage. Thus, this program contributes to improving the quality of religious tourism while encouraging community empowerment as key actors in cultural and spiritual-based village development.